Tatya Tope and Kanpur in the 1857 War of Independence : 1857 के स्वतंत्रता संग्राम में तात्या टोपे और कानपुर - Poonam; Tripathi, Tripuresh (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Till 1857, people were unfamiliar with the name of Tatya Tope. But the dramatic events of 1857 suddenly brought him out of darkness into the light. Before the start of the First War of Independence, he was only a companion of Raja Nana Saheb of Bithoor, the eldest son of the deposed Bajirao II, but after Kanpur joined the War of Independence, Tatya reached the position of Commander-in-Chief of the Peshwa's army. All the events of the subsequent wars raised his name to the forefront like a comet, which left a long line of light behind it. His name became famous not only in the country but also outside the country. Not only friends, but enemies also tried to see and understand his military campaigns with curiosity and eagerness.Abstract in Hindi Language:1857 ई. तक लोग तात्या टोपे के नाम से अपरिचित थे। लेकिन 1857 की नाटकीय घटनाओं ने उन्हें अचानक अंधकार से प्रकाश में लाकर खड़ा कर दिया। प्रथम स्वतंत्रता संग्राम के प्रारंभ होने से पूर्व वे राज्यच्युत बाजीराव द्वितीय के सबसे बड़े पुत्र बिठूर के राजा नाना साहब के एक प्रकार से साथी-मुसाहिब मात्र थे, किंतु स्वतंत्रता संग्राम में कानपुर के सम्मिलित होने के पश्चात् तात्या पेशवा की सेना के सेनाध्यक्ष की स्थिति तक पहुंच गए। उसके पश्चातवर्ती युद्धों की सभी घटनाओं ने उनका नाम सबसे आगे एक पुच्छल तारे की भांति बढ़ाया, जो अपने पीछे प्रकाश की एक लंबी रेखा छोड़ता गया। उनका नाम केवल देश में नहीं वरन् देश के बाहर भी प्रसिद्ध हो गया। मित्र ही नहीं, शत्रु भी उनके सैनिक अभियानों को जिज्ञासा और उत्सुकता से देखने और समझने का प्रयास करते थे।Keywords:- तात्या टोपे, स्वतंत्रता संग्राम, ब्रिटिश सत्ता, कानपुर, गुरिल्ला रणनीति।
Keywords: Tatya Tope; War of Independence; British rule; Kanpur; Guerrilla strategy